ANALISIS PENGGUNAAN STRATEGI GENERIK TERHADAP KINERJA PADA LEMBAGA PENDIDIKAN LUAR SEKOLAH DI KOTA MALANG - Ike - Septiyorini; Mohammad - Fatchi; Djumilah - Zain (Wacana Journal of Social and Humanity Studies, 2009)
ABSTRACT Â  This study identifies factual description of strategic competition among various Vocational Education Institution in Malang Regency. Using Porter Generic Strategy either partial or combination, this study also reviews Porter Generic Strategy difference that is used partially and in combination with the performance level of the studied vocational education institution. This study is conducted in vocational education institution in Malang Regency eith the number of sample 30 managers from 6 vocational institutions. To ideentify the strategy in vocational education institution based on the use of Porter Generic Strategy, this study used Cluster analyzer method. After being classified base on different strategy among vocational education istitution. Than these strategies are compared by using Manova analysis to find out the performance in vocational education institution. This study indicated that : (1) The vocational education institution applying 13.33% of Difference Strategy from population has excellence in level of students growth; (2) the vocational education institution applying 70.00% of Difference and Focus Strategy from population has average excellence in all performance citeria; (3) The vocational education institution applying 16.66% of Difference and Cost Strategy from population has excellence in level of students growth, the control of operational cost, the control of administration cost, customer (students) recruitment and resources improvement.